2019
DOI: 10.1111/jasp.12617
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity to dating and marriage across the religious divide in Northern Ireland: The role of intergroup contact

Abstract: Intergroup contact has long been recognized as an important factor in promoting positive intergroup attitudes. However, in operationalizing intergroup attitudes, previous studies have rarely investigated attitudes toward one of the most intimate forms of contact, romantic relationships. In this study (N = 176), we expand the intergroup contact literature to examine the association between intergroup contact and, arguably, a litmus test of intergroup attitudes: receptivity to intergroup romance. We do so in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 40 publications
5
30
0
Order By: Relevance
“…Trust is particularly relevant in intergroup relations because it implies positive expectations about intentions and others' behavior (Kenworthy et al, 2016) and fosters cooperation between members of different groups (e.g., Ferrin et al, 2008). Numerous studies supported the mediating role of intergroup trust in the relationship between both direct (Çakal et al, 2019;Yucel & Psaltis, 2019) and indirect forms of contact , and attitudinal Paterson et al, 2019) and behavioral intergroup outcomes (Kenworthy et al, 2016;McKeown & Psaltis, 2017;Turner et al, 2013). Relatedly, greater outgroup morality (perceiving the outgroup as honest, trustworthy, and sincere) also explains the effect of positive intergroup contact on outgroup attitudes (Brambilla et al, 2013;Vezzali et al, 2019).…”
Section: Mediators Of Primary and Secondary Transfer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is particularly relevant in intergroup relations because it implies positive expectations about intentions and others' behavior (Kenworthy et al, 2016) and fosters cooperation between members of different groups (e.g., Ferrin et al, 2008). Numerous studies supported the mediating role of intergroup trust in the relationship between both direct (Çakal et al, 2019;Yucel & Psaltis, 2019) and indirect forms of contact , and attitudinal Paterson et al, 2019) and behavioral intergroup outcomes (Kenworthy et al, 2016;McKeown & Psaltis, 2017;Turner et al, 2013). Relatedly, greater outgroup morality (perceiving the outgroup as honest, trustworthy, and sincere) also explains the effect of positive intergroup contact on outgroup attitudes (Brambilla et al, 2013;Vezzali et al, 2019).…”
Section: Mediators Of Primary and Secondary Transfer Effectsmentioning
confidence: 99%
“…Multiple other mechanisms explaining specifically primary (but not secondary) transfer effects of positive contact have been identified. These comprise affective variables such as different intergroup emotions (e.g., anger: Barlow et al, 2019;disgust and admiration: Cernat, 2011;fear: Kauff et al, 2017;Seger et al, 2017) and numerous cognitive processes (e.g., knowledge about the outgroup: Brown & Hewstone, 2005); social norms (perceptions of how ingroup members think and act: Christ et al, 2014;Paterson et al, 2019;Turner et al, 2008;Wang et al, 2019); inclusion of the other in the self (perceived closeness between the self and outgroup: Page-Gould et al, 2010;Turner et al, 2008); self-disclosure (disclosure of personal information about self to other: Frølund Thomsen, 2012;Turner, et al, 2007); dehumanization or infrahumanization (denying elements of humanness to outgroups: Prati & Loughnan, 2018;Stathi et al, 2017); perceived importance of and satisfaction with contact (Frias-Navarro et al 2020;van Dick et al, 2004); perceived outgroup heterogeneity (perception of similarity between outgroup members: Čehajić et al, 2008); stereotypes of outgroup warmth and competence (Kotzur et al, 2019;Zingora et al, 2020); and metastereotypes (beliefs about the stereotypes that outgroup members hold about their group: Mazziotta et al, 2011). It is plausible to expect many of these processes (e.g., emotions, social norms, outgroup evaluations) to generalize from primary to secondary outgroups and thus underlie not only the primary but also secondary transfer effects.…”
Section: Mediators Of Specifically Primary Transfer Effectsmentioning
confidence: 99%
“…Hodson et al (2009) found that for university students with higher (vs. lower) heterosexual identity, contact and friendship with gay people was associated with less prejudice. Furthermore, studies conducted in Northern Ireland showed that contact between Catholics and Protestants positively predicted intergroup forgiveness but only among those more highly identified with their community (Voci, Hewstone, Swart, & Veneziani, 2015), and also predicted greater receptivity to cross‐community relationships and more favorable attitudes toward the other community yet more strongly so among higher identifiers (Paterson, Turner, & Hodson, 2019).…”
Section: Individual Differences As Moderators Of the Contact–prejudicmentioning
confidence: 99%
“…The positive associations with contact extend beyond more positive attitudes towards the other community. In a further study conducted among Catholic and Protestant undergraduate students in Northern Ireland, experiencing positive contact with the other community predicted greater perceived likelihood of dating someone from the other community, and greater perceived appropriateness of marrying someone from the other community (Paterson et al 2019). These relationships were explained by the perception that family and friends were positively predisposed towards the idea of cross-community relationships.…”
Section: Benefits For Intergroup Relationsmentioning
confidence: 84%
“…The research reviewed highlights that past contact experiences, learning about the positive contact experiences of others and reduced anxiety promote greater confidence in contact, which in turn predicts more positive contact (Bagci et al 2019). This is important given the benefits that intergroup contact can bestow in terms of more positive intergroup relations (Brown & Hewstone 2005, Paterson et al 2019, Pettigrew & Tropp 2006, Turner et al 2007a, 2007b, 2013a. Moreover, interventions which draw on intergroup contact theory but do not involve (initially, at least) face-to-face encounters with outgroup members can help to reduce stress, bolster confidence in contact and promote more positive intergroup encounters (Turner & West 2012, West & Turner 2014, West et al 2015.…”
Section: Summary and Suggestions For Future Researchmentioning
confidence: 99%